An analysis of the structural, thermal and optical characteristics as well as the electrical resistivity of tert-butyldiphenylsilyl substituted poly(norbornene-dicarboximide)s. (15th January 2015) - Spring, Andrew M.; Maeda, Daisuke; Ozawa, Masaaki; Odoi, Keisuke; Qiu, Feng; Yamamoto, Kazuhiro; Yokoyama, Shiyoshi
Abstract: A sequence of well controlled tert -butyldiphenylsilyl substituted poly(norbornene-dicarboximide)s with ascending molecular weights have been prepared using the Grubbs 1st generation catalyst in anhydrous chloroform. The kinetics of the polymerization was examined using nuclear magnetic resonance spectroscopy and gel permeation chromatography. By decreasing the Grubbs catalyst concentration, the polymer molecular weights increased linearly. The glass transition temperatures and thermal decomposition temperatures initially increased with polymer molecular weight, then reached a plateau. Regardless of molecular weight the polydispersities remained narrow. The polymers exhibited a predominantly trans microstructure and matrix-assisted laser desorption/ionization mass spectrometry was utilized to determine polymer end groups and to calculate the absolute molecular weights. The residual ruthenium content of the polymers was quantified using inductively coupled plasma mass spectrometry and the influence on the resistivity, refractive indices and thin film optical transmittance was evaluated. Graphical abstract: